2014
DOI: 10.3109/01942638.2014.904471
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sensory Processing Problems in Children With and Without Attention Deficit Hyperactivity Disorder

Abstract: The results suggest the importance of assessing sensory processing issues in children with ADHD to guide in the intervention process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 27 publications
(32 reference statements)
2
55
0
3
Order By: Relevance
“…Two recent RCTs and two non-randomized clinical trials, not included in the above reviews 18,9294 compared VR and SG interventions to control conditions with children with CP 18,92,93 and children with Fetal Alcohol Spectrum Disorder (FASD) who had motor disabilities. 94 Mixed results for children with CP using MiTii exercise are reported.…”
Section: Outcomes Of Vr and Sg Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent RCTs and two non-randomized clinical trials, not included in the above reviews 18,9294 compared VR and SG interventions to control conditions with children with CP 18,92,93 and children with Fetal Alcohol Spectrum Disorder (FASD) who had motor disabilities. 94 Mixed results for children with CP using MiTii exercise are reported.…”
Section: Outcomes Of Vr and Sg Interventionsmentioning
confidence: 99%
“…Five used the Canadian Occupational Performance Measures, which includes the collaborative creation of individualized goals, 18,59,70,95,96 one study used the Test of Playfulness 58 and two used the Assessment of Motor and Process Skills. 18,92 . Most studies indicated a positive improvement in participation.…”
Section: Outcomes Of Vr and Sg Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These sensory processing differences can have significant and lifelong consequences for learning and social abilities, and are often shared by children who meet Diagnostic and Statistical Manual-Fifth Edition (DSM-5; [3]) criteria for conditions such as Autism Spectrum Disorder and Attention Deficit/Hyperactivity Disorder (ADHD; [46]). Although there is symptom overlap, children with SPD often fail to receive services despite having similar behavioral impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, convenience samples of clinically referred children with ADHD estimate that between 46–69% also show symptoms of sensory over-responsivity [7,8]. Characterization of the comorbidity between attentional abilities and sensory abnormalities in children often rely upon parent report questionnaires for ease of administration [69]. Recent work has demonstrated that some children with SPD have measurable structural differences in white matter tracts that correlate with attention abilities [10].…”
Section: Introductionmentioning
confidence: 99%